2022
DOI: 10.1186/s12889-022-14064-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity and its facilitators and barriers among Syrian refugees living in Amman City, Jordan: a cross-sectional study

Abstract: Background Physical inactivity is one of the major risk factors for non-communicable diseases. Few studies about physical activity have been conducted among refugees from neighbouring countries. Given changes in the situation of Syrians, assessment of physical activity among Syrian refugees is required to understand their situation. This study aimed to evaluate the degree of self-reported physical activity and to identify perceived facilitators of and barriers to physical activity among Syrian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Yet, further research is needed in this area as a literature search yielded only two studies published since our 2017 report which identified mood as a facilitator of healthy lifestyle behavior among immigrant populations. One study examined nutrition and one examined physical activity; no studies on social support facilitating health behaviors among immigrant populations were noted [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, further research is needed in this area as a literature search yielded only two studies published since our 2017 report which identified mood as a facilitator of healthy lifestyle behavior among immigrant populations. One study examined nutrition and one examined physical activity; no studies on social support facilitating health behaviors among immigrant populations were noted [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%